If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 + -9x = 18 + 10x Solving 37 + -9x = 18 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 37 + -9x + -10x = 18 + 10x + -10x Combine like terms: -9x + -10x = -19x 37 + -19x = 18 + 10x + -10x Combine like terms: 10x + -10x = 0 37 + -19x = 18 + 0 37 + -19x = 18 Add '-37' to each side of the equation. 37 + -37 + -19x = 18 + -37 Combine like terms: 37 + -37 = 0 0 + -19x = 18 + -37 -19x = 18 + -37 Combine like terms: 18 + -37 = -19 -19x = -19 Divide each side by '-19'. x = 1 Simplifying x = 1
| 37-9x=18+10x | | 2x+10=6x+5 | | -6x+1.2=4.2 | | 2x+10=6x+5 | | -6x+1.2=4.2 | | 500+350m=430m | | (3xy)(7z)= | | (x-5z)(7x-5z)= | | -2v+8-4=20 | | 12x^2=12x^2 | | 25-2p=-7p+p-15 | | 4c(c-3)=6-2c | | -74=-14+5k | | 5.3y+0.37=3.02y-2.48 | | (7w+4)(3w-9)=0 | | 6m^3-5m^2+-4m=0 | | 5z=4z+-12 | | -x+3=2x-6 | | -5x+4x-16+2x-6x+27= | | 234=44x+48y | | 5z=-4z+12 | | 5x^2+(2k-3)x-2k+3=0 | | 2x+6=-4x-4x | | 4x^2-40+60=0 | | 8x-3x=2x-5 | | 11x+2=7x | | 8y+4.6=-68.2 | | .004(7-k)+.006(k-6)=1 | | 2x+3x^2(4x-5)=0 | | (2x^2)-11x+5=0 | | 6b+5b=43 | | 6y+8x-9y+(-10x)= |